2022
DOI: 10.1093/rheumatology/keac024
|View full text |Cite
|
Sign up to set email alerts
|

Drug levels, anti-drug antibodies and B-cell counts were not predictive of response in rheumatoid arthritis patients on (ultra-)low-dose rituximab

Abstract: Objectives The REDO trial showed that ultra-low dose rituximab (500 mg or 200 mg) was similarly effective in the majority of rheumatoid arthritis (RA) patients. This pre-planned secondary analysis investigates 1) associations between rituximab dosage, drug levels, anti-drug antibodies (ADA) and B cell counts and 2) the predictive value of pharmacokinetic and -dynamic parameters, patient, disease and treatment characteristics in relation to response to ultra-low dose rituximab. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…This likely indicates that rituximab is applied at saturation in our study population. As other previous studies demonstrate similar clinical efficacy of lower rituximab doses in AAV and RA (30,31), our findings encourage further studies investigating the clinical efficacy of low-dose rituximab treatment in autoimmune diseases, especially in long-term use for remission maintenance.…”
Section: Discussionsupporting
confidence: 86%
“…This likely indicates that rituximab is applied at saturation in our study population. As other previous studies demonstrate similar clinical efficacy of lower rituximab doses in AAV and RA (30,31), our findings encourage further studies investigating the clinical efficacy of low-dose rituximab treatment in autoimmune diseases, especially in long-term use for remission maintenance.…”
Section: Discussionsupporting
confidence: 86%
“…The association between 200 mg RTX and positive response after two-dose and three-dose vaccination could be explained by faster B cell repletion. Previous studies showed The RTX-COVAC-2 study that B cell repopulation is associated with humoral response [3,9] and that B cell numbers are non-significantly higher at 6 months after a dose of 200 mg RTX compared with 1000 mg [10]. Unfortunately, B cell counts were not performed in our current study.…”
Section: Discussionmentioning
confidence: 62%
“…To mitigate this insecurity, rheumatologists indicated a need for predictors of successful dose reduction. Although Vital et al demonstrated that the degree of B-cell depletion determines the clinical response more strongly than the dose of rituximab (Vital et al, 2011), recent research has not been able to identify significant predictors for the response to ultra-low doses of rituximab (Wientjes et al, 2022). The lack of experience with rituximab among our participating rheumatologists might in turn be explained by perceptions about other available advanced therapies, as Belgian rheumatologists perceived an intravenous administration route as less satisfactory for patients in terms of disease control compared to subcutaneous administration of bDMARDs (De Mits et al, 2016).…”
Section: Discussionmentioning
confidence: 99%